Performance enhancement of interdigitated flow channel of PEMFC by scaling up study. Issue 14 (17th July 2020) - V., Lakshminarayanan; P., Karthikeyan
ABSTRACT: The performance of Proton Exchange Membrane Fuel Cell (PEMFC) with various ribs-to-channel-width ratios on the interdigitated flow field has been investigated by scaling-up from 25 cm 2 to 36 cm 2 and from 25 cm 2 to 49 cm 2 using Computational Fluid Dynamics (CFD) fluent-14.0 software. The peak power density is reduced by 18% and 25.5% when scaling up from 25 cm 2 to 36 cm 2 and from 25 cm 2 to 49 cm 2 active area of PEMFC, respectively. The validation has been done on the 25 cm 2 active area with interdigitated flow channel of PEMFC. The combined effect of design and operating parameters of various combinations on an interdigitated flow channel for the performance enhancement of 25 cm 2 PEMFC has been studied using optimization technique. For the reliability of the numerical results, experimental validation of 36 cm 2 PEMFC with interdigitated flow field is carried out for the rib-to-channel-width ratio of 1:2, pressure of 2.5 bar, temperature of 343 K, and stoichiometric ratio of reactants of 3.5.